Introduction. Théorie et réalité de l'égalité juridique des langues au Canada - Prujiner, Alain (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
This introduction includes a résumé ofpanels and debates of the colloquium organised conjointly by the Faculty of law and the International Center for Reseach on Bilingualism in November 1982. Papers presented at that occasion are published thereafter.